Linear cavity multiwavelength thulium-doped fiber laser incorporating a highly nonlinear fiber - Radzali, Rozlinda (2017)
2-μm laser generation has attracted intense research interest due to its ability to fulfill shorter wavelength needs such as laser cutting and surgery whilst providing eye-safer operation. Additionally, in applications such as light detection and ranging (LIDAR), sensing, spectroscopy, and material processing, certain materials interact better in 2-μm wavelength band, thus delivering better accuracy and precision in the results. In recent times, the constant need for more data or information has evoked exploration on the use of 2-μm region as an expansion to the optical fiber communication band, further promoting interest in 2-μm thulium-doped fiber lasers. One major issue in multiwavelength thulium-doped fiber laser (MWTDFL) however, is the high loss of silica in that region. This consequently impedes the generation of high gain that is essential in producing multiple channels. Resultantly, most works had to resort to complex nonlinear structure in order to address this issue, thus lessening the feasibility of translating these laser devices into industrial applications. This work proposed a simple thulium-doped fiber laser configuration capable of generating multiwavelength output. A linear cavity configuration was employed for this purpose with two loop mirrors confining the oscillation for the thulium-doped fiber induced gain. An optical interleaver was included to generate the multiwavelength seed signal, allowing four distinct lasing peaks to be observed albeit with instability to the two lower power peaks. The work then progressed to the integration of highly nonlinear fiber (HNLF) within the structure. A 500-m section of HNLF was spliced in the laser setup to investigate its performance. The presence of HNLF helped to increase the number of output channels to 22 and 35 lasing lines in 10-dB and 20-dB bandwidth respectively with optical signal to noise ratio as high as 30-dB. Maximum output power observed is 0.406 mW. The high nonlinearity from the presence of HNLF induced four-wave mixing (FWM) effect which assisted gain distribution allowing higher channel count to be produced. The stability of the HNLF-integrated MWTDFL was then investigated. This experiment was performed by observing the multiwavelength laser spectrum every 5 minutes for a total time span of one hour at the maximum pump power of 2000 mW. Based on the findings, the laser exhibited power fluctuations of less than 1.325-dB, with the worst value recorded at shorter wavelength region due to the lower net gain profile. Maximum wavelength dithering of 0.12 nm was also observed thanks to the use of physical multiwavelength selector. In summary, the work has demonstrated the use of a simple linear cavity design to generate multiwavelength output achieved by integrating a section of HNLF within the cavity without complex nonlinear-based structure. High channel count was generated with minimal fluctuation to the peak power and wavelength. The success of this work can elevate the status of MWTDFL as a feasible candidate for industrial applications requiring 2-μm laser band.